External counterpulsation for the treatment of patients with refractory angina - Rovshan Alakbarov; Tofig Jahangirov; Orazbek Sakhov; Sholpan Zhangelova (National Scientific Medical Center, 2018)
Despite the great advances in conventional medical and invasive treatment of patients with coronary heart disease, a significant number of these patients continues to have a resistant to standard therapy angina pectoris. Many of these patients are not candidates for subsequent myocardial revascularisation procedures for many reasons, and optimal medical treatment is not allowed to effectively control the symptoms of angina pectoris. To treat this category of patients, a large number of different treatment methods have been proposed. External counterpulsation is one of the methods of treatment of patients with refractory angina.